COLLABORATIVE GOVERNANCE OF SEDUDO WATERFALL TOURISM MANAGEMENT IN THE PERSPECTIVE OF PUBLIC ADMINISTRATION - Wulan Putri Aprida Sari; Septi Wulandari; Heny Suhindarno (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The management of tourist destinations requires a governance pattern that involves various stakeholders so that it can run effectively and sustainably. Sedudo Waterfall Tourism in Nganjuk Regency is a natural tourist destination whose management involves local governments, village governments, and traditional leaders. The involvement of these various actors makes collaboration an important aspect in tourism management. This study aims to analyze the application of collaborative governance in the management of Sedudo Waterfall Tourism by focusing on initial conditions, institutional design, facilitative leadership, collaborative processes, and collaboration results. The research method used is qualitative with a phenomenological approach to understand the experience and dynamics of the interaction of the actors involved, and is supported by data analysis using NVivo 12 Pro. The results of the study show that collaboration has been relatively harmonious, but there is still an imbalance of authority and resources, especially between local governments and traditional leaders. These findings suggest that stronger institutional and regulatory design is needed to support sustainable tourism management from a public administration perspective.